PERANCANGAN OKTAGRAM SEBAGAI MEDIA PEMBELAJARAN GEOMETRI SEKOLAH DASAR - Astuningtyas, Erika Laras (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2015)
Abstract:This study aims to determine: (1) Octagrams development with ADDIE models, (3)which havea better mathematics achievement in Geometry, who teachuses Octagram or the ones withtraditional approach.This study is a research and development of Octagramuses ADDIE(Analysis, Design, Development, Implementation, and Evaluation) method. This study islimited on development. The instruments used are a mathematics achievement test,students questionnaire, and validity questionnaire. Qualitative data analysis used aredatastudy,data reduction, and conclution. Mathematics achievement analysis uses t-test. The testrequirements include a population with normality of the Liliefors test, test of homogeneity ofvariance. Based on the results of study, it can be concluded that (1) development ofOctagram with ADDIE models in Geometry lesson consist of three steps. Analysis is todeterminewhat kinds of development will do. Design is construct draftof Octagram.Development are validate instrument by expert judgement and limited desemination, (2) Theuses of Octagramin Graph Theory lecture gives a better mathematics achievement thanthetraditional approach.Keywords : Octagram, ADDIE, Geometry